(2-w)(2w+3)=0

Simple and best practice solution for (2-w)(2w+3)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (2-w)(2w+3)=0 equation:



(2-w)(2w+3)=0
We add all the numbers together, and all the variables
(-1w+2)(2w+3)=0
We multiply parentheses ..
(-2w^2-3w+4w+6)=0
We get rid of parentheses
-2w^2-3w+4w+6=0
We add all the numbers together, and all the variables
-2w^2+w+6=0
a = -2; b = 1; c = +6;
Δ = b2-4ac
Δ = 12-4·(-2)·6
Δ = 49
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$w_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$w_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

$\sqrt{\Delta}=\sqrt{49}=7$
$w_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(1)-7}{2*-2}=\frac{-8}{-4} =+2 $
$w_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(1)+7}{2*-2}=\frac{6}{-4} =-1+1/2 $

See similar equations:

| -(5/4)x+(2/5)=-(13/30) | | -7+5x=11-x | | 8x-6=57-x | | -b/5=-9 | | 5x=(3×4)2x | | 201-w=145 | | -u+170=11 | | 5.4-3c=9.3 | | 5^(3x-2)=125^(2x) | | v/3+7=-1 | | 4x(x-3)(2x+7)=0 | | 4-2=4-2x | | -21=7(y-1) | | 5v-5+4(2v+1)=-5(v+2) | | 7-3x=10-3x | | 4-5v=-6 | | 7-3x=10-3 | | -2/5+2/3x=-3/2 | | 1/2(5x-10)=4x-14 | | -29=4u-1 | | 1/2(5x-10)=4x-14) | | x^2+12x-156=0 | | -4(w+1)=36 | | 5=7-2v | | 6x+4+8x-2=44 | | 3x^2+13x-7=0 | | 2+2(7w-2)=-5(2w-2)+6w | | 3q^2-4q=2q^2-8q+21 | | 1x+20=4x+5 | | 2+2(7w-2)=-5(2w-2)+6 | | 7(6-4n)=-18+2n | | -2(-2w+4)-6w=4(w-4)-6 |

Equations solver categories